1989
DOI: 10.1128/aem.55.4.946-952.1989
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial metabolism of hydroxylated biphenyls

Abstract: Isolates able to grow on 3or 4-hydroxybiphenyl (HB) as the sole carbon source were obtained by enrichment culture. The 3-HB degrader Pseudomonas sp. strain FH12 used an NADPH-dependent monooxygenase restricted to 3-and 3,3'-HBs to introduce an ortho-hydroxyl. The 4-HB degrader Pseudomonas sp. strain FH23 used either a mono-or dioxygenase to generate a 2,3-diphenolic substitution pattern which allowed meta-fission of the aromatic ring. By using 3-chlorocatechol to inhibit catechol dioxygenase activity, it was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In contrast, 4-hydroxybiphenyl was shown to be dioxygenated at the nonhydroxylated ring to yield 2,3,4'-trihydroxybiphenyl (12). The mass spectra of the latter compound and that of 2,3,3'-trihydroxybiphenyl, obtained from the oxidation of 3-hydroxy-and 3,3'-dihydroxybiphenyl (12), respectively, closely resemble the spectrum of our 2,2',3-trihydroxybiphenyl. With identical to those previously reported for 2,3-l phenyl (19).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In contrast, 4-hydroxybiphenyl was shown to be dioxygenated at the nonhydroxylated ring to yield 2,3,4'-trihydroxybiphenyl (12). The mass spectra of the latter compound and that of 2,3,3'-trihydroxybiphenyl, obtained from the oxidation of 3-hydroxy-and 3,3'-dihydroxybiphenyl (12), respectively, closely resemble the spectrum of our 2,2',3-trihydroxybiphenyl. With identical to those previously reported for 2,3-l phenyl (19).…”
Section: Discussionmentioning
confidence: 68%
“…During this process, the regeneration of NADH + H+ seems to be impossible. Formation of the above trihydroxybiphenyl was recently proposed to be an intermediate in the degradation of 2-hydroxybiphenyl by dioxygenation and of 2,2'dihydroxybiphenyl by a monooxygenase reaction which is also involved in the formation of 2,3-dihydroxybiphenyl from 3-hydroxybiphenyl (12,19). In contrast, 4-hydroxybiphenyl was shown to be dioxygenated at the nonhydroxylated ring to yield 2,3,4'-trihydroxybiphenyl (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a mixture of halogenated benzoates might accumulate if the indigenous bacteria was ineffectual in degrading them. Several studies have focused on the metabolic pathways of 2-chlorobenzoate (4,9,12,18,24,29), 3-chlorobenzoate (3,5,8,13,20,21), and 4-chlorobenzoate (10,14,16,17,25,26,28), whereas less is known about the metabolism of the dichlorobenzoates (18). Hartmann et al (10) were the first to show that 3,5-dichlorobenzoate degraded via 3,5-dichlorocatechol to form the corresponding chlorinated cis,cis-muconic acids in Pseudomonas sp.…”
mentioning
confidence: 99%
“…Adriaens and Focht [16] demonstrated that 3-chloro-4-hydroxybenzoate was a pseudosubstrate for the 4-hydroxybenzoate monooxygenase, by evoking oxygen and NADH consumption, yet it was not hydroxylated. Alternatively, Higson and Focht [17] described substrate inhibition of the 3-hydroxybiphenyl monooxygenase at 3-hydroxybiphenyl concentrations higher than 4 /~M. Recently, Folsom et al [18] reported on the interactions between trichloroethylene (TCE) and phenol, since TCE degradation requires enzymes involved in toluene, cresol, and phenol utilization.…”
Section: Introductionmentioning
confidence: 99%